2012
DOI: 10.1002/ccd.24416
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic effects of adjunctive cilostazol therapy in patients with coronary artery disease on dual antiplatelet therapy: Impact of high on‐treatment platelet reactivity and diabetes mellitus status

Abstract: Cilostazol reduces platelet reactivity both in HPR and non-HPR patients, although these PD effects are enhanced in HPR patients with DM. Nevertheless, larger studies are needed to better evaluate possible differential effects of cilostazol on platelet reactivity by diabetes status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The OPTIMUS-2 study 96 found that the addition of cilostazol to DAPT improved inhibition of platelet P2Y 12 signalling. Moreover, cilostazol might decrease platelet aggregability in patients with diabetes and HPR when taking clopidogrel 97 . Clinical benefits of cilostazol in addition to DAPT were observed in a nonrandomized study of Asian patients undergoing PCI, mainly in terms of reduced rates of target-lesion revascularization and stent thrombosis 98 ; in randomized studies, this improvement in outcomes was found to be greatest for patients with diabetes [99][100][101] .…”
Section: Acsmentioning
confidence: 99%
“…The OPTIMUS-2 study 96 found that the addition of cilostazol to DAPT improved inhibition of platelet P2Y 12 signalling. Moreover, cilostazol might decrease platelet aggregability in patients with diabetes and HPR when taking clopidogrel 97 . Clinical benefits of cilostazol in addition to DAPT were observed in a nonrandomized study of Asian patients undergoing PCI, mainly in terms of reduced rates of target-lesion revascularization and stent thrombosis 98 ; in randomized studies, this improvement in outcomes was found to be greatest for patients with diabetes [99][100][101] .…”
Section: Acsmentioning
confidence: 99%
“… Lee 2007 [ 34 ] 166 9 MACEs, TVR, TLR, ST, D/MI/TVR, BL and ADR. Yang 2011 [ 35 ] 154 PRU and PA Yang 2007 [ 36 ] 55 7 PA Capranzano 2012 [ 37 ] 80 1 PRU and PRI Angiolillo 2008 [ 38 ] 40 1 PRI and PA Angiolillo 2011 [ 39 ] 106 1 PRI Ha 2013 [ 40 ] 84 2 PRU and PA Abbreviations : MACEs major adverse cardiac effects, TVR target vessel revascularization, TLR target lesion revascularization, BL bleeding, ST stent thrombosis, ADR adverse drug reactions, D death, MI myocardial infarction, PA platelet aggregation, PRI platelet reactivity index, PRU platelet reactivity unit …”
Section: Resultsmentioning
confidence: 99%
“…An analysis of data on the adjunctive role of cilostazol in 79 patients receiving DAPT with aspirin and clopidogrel, as per the pharmacodynamic effects of cilostazol on high on-clopidogrel platelet reactivity (HPR) levels and as per the T2D status, indicated that cilostazol reduced platelet reactivity both in HPR and non-HPR patients, and these effects were amplified in HPR patients with T2D. 146 Furthermore, cilostazol has been suggested to prevent the progression of coronary atherosclerosis in people with T2D. 147 In summary, in patients with T2D, DAPT with cilostazol and aspirin seems to be equivalent or better than clopidogrel and aspirin with lower rates of MACEs and restenosis, while triple therapy with cilostazol added to DAPT appears to be superior to DAPT with enhanced antiplatelet effect and lower restenosis rates.…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 99%
“…An analysis of data on the adjunctive role of cilostazol in 79 patients receiving DAPT with aspirin and clopidogrel, as per the pharmacodynamic effects of cilostazol on high on‐clopidogrel platelet reactivity (HPR) levels and as per the T2D status, indicated that cilostazol reduced platelet reactivity both in HPR and non‐HPR patients, and these effects were amplified in HPR patients with T2D 146 . Furthermore, cilostazol has been suggested to prevent the progression of coronary atherosclerosis in people with T2D 147 …”
Section: Coronary Artery Diseasementioning
confidence: 99%